2019
DOI: 10.1111/wrr.12737
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of Calendula officinalis extract for wound healing

Abstract: Use of complementary and alternative medicine for wound healing is influencing mainstream medical practice. This systematic review evaluates the role of Calendula officinalis flower extract as monotherapy compared to control for wound healing in vivo. Searches were conducted in PubMed, EMBASE, Cochrane Central Register of Controlled Trials, CINAHL, and Scopus (up to April 2018) with 14 studies meeting the inclusion criteria, comprising 7 animal experiments and 7 clinical trials. Findings from the review on acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 31 publications
0
84
0
7
Order By: Relevance
“…We present the comparison with scientific literature (for the complete data, please see Table S1 ): Achillea millefolium digestive, anti-inflammatory for several problems (stomachache, muscular pain, rash) and disinfectant [ 19 , 23 , 24 , 25 ]; Achillea moschata antioxidant and antibacterial [ 26 ]; Alchemilla vulgaris anti-inflammatory [ 27 , 28 ]; Arnica montana anti-inflammatory for wounds, cutaneous traumas, muscular, and articular pain [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]; Artemisia absinthium digestive [ 31 , 37 , 38 , 39 ] (however, in a review from 2016 the potential antiulcer effect, with the decrease in the production of gastric juice, is reported [ 40 ]); Artemisia genipi digestive and colds [ 39 , 41 ]; Betula pendula diuretic [ 42 ]; Calendula officinalis anti-inflammatory and disinfectant for wounds, rashes, and burns, improves circulation [ 31 , 43 , 44 , 45 , 46 , 47 , 48 ]; Carduus nutans antimicrobial and anti-inflammatory [ 49 ]; Cetraria islandica expectorant [ 50 , 51 , 52 ] and anti-inflammatory [ 51 , 53 ]; Chelidonium majus skin tags and warts [ 54 , 55 ]; Cichorium intybus depurative of the urinary tract […”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We present the comparison with scientific literature (for the complete data, please see Table S1 ): Achillea millefolium digestive, anti-inflammatory for several problems (stomachache, muscular pain, rash) and disinfectant [ 19 , 23 , 24 , 25 ]; Achillea moschata antioxidant and antibacterial [ 26 ]; Alchemilla vulgaris anti-inflammatory [ 27 , 28 ]; Arnica montana anti-inflammatory for wounds, cutaneous traumas, muscular, and articular pain [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]; Artemisia absinthium digestive [ 31 , 37 , 38 , 39 ] (however, in a review from 2016 the potential antiulcer effect, with the decrease in the production of gastric juice, is reported [ 40 ]); Artemisia genipi digestive and colds [ 39 , 41 ]; Betula pendula diuretic [ 42 ]; Calendula officinalis anti-inflammatory and disinfectant for wounds, rashes, and burns, improves circulation [ 31 , 43 , 44 , 45 , 46 , 47 , 48 ]; Carduus nutans antimicrobial and anti-inflammatory [ 49 ]; Cetraria islandica expectorant [ 50 , 51 , 52 ] and anti-inflammatory [ 51 , 53 ]; Chelidonium majus skin tags and warts [ 54 , 55 ]; Cichorium intybus depurative of the urinary tract […”
Section: Resultsmentioning
confidence: 99%
“…We focused our attention particularly on systematic reviews and meta-analysis, when possible, or on single in vitro, in vivo, and clinical trials studies, applying no time filters. Based on this data, specific and detailed tables were produced ( Table 4 and Supplementary Materials Table S1 [ 2 , 3 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , ...…”
Section: Methodsmentioning
confidence: 99%
“…Due to the high potential of Calendulae flos use in wound care, a number of clinical studies have been conducted. Eight clinical trials were conducted assessing the usefulness of Calendulae flos extracts in the wound healing process, including clinical trials evaluating acute and chronic wounds [24,25]. Findings from the studies on acute wound healing showed faster resolution of the inflammation phase with increased production of granulation tissue in the test groups treated with the extract [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Eight clinical trials were conducted assessing the usefulness of Calendulae flos extracts in the wound healing process, including clinical trials evaluating acute and chronic wounds [24,25]. Findings from the studies on acute wound healing showed faster resolution of the inflammation phase with increased production of granulation tissue in the test groups treated with the extract [24,25]. Clinical control studies on venous ulcers demonstrated decreased ulcer surface area compared to controls [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation